Molecular cytogenetic analysis and clinical manifestations of a case with de novo mosaic ring chromosome 7 - Tsai, Li-Ping (BioMed Central, 2011)
AIM: Clinical and molecular cytogenetic investigations of a newborn girl exhibiting facial dysmorphism with developmental delay. METHODS: Phenotypic evaluation was first applied to examine the proband's developmental status. Computed tomography and colour transcranial Doppler were used then to investigate her brain structure and function. Subsequently, chromosomal abnormalities were examined by karyotyping and fluorescent in situ hybridization was performed to investigate size of fragments lost at the two distal ends of the ring chromosome 7. In addition, multicolour banding was applied to rule out structural rearrangement occurs in between the ring chromosome 7. RESULTS: The proband was born with mosaic supernumerary ring chromosome 7, without a normal karyotype detected in the peripheral blood lymphocytes. The distal arm of chromosome 7p (at least 255 kb from the telomere) was part of an extra ring chromosome 7. In addition, the distal arm of 7q, at least 8 kb from the telomere, was missing. There was no other chromosomal rearrangement detected by multicolour banding. INTERPRETATION: This is the 19(th )reported case of complete ring chromosome 7 mosaicism and the first survived case with mosaic supernumerary ring 7 without a normal karyotype detected in the peripheral lymphocytes.